College instructors’ perspectives on the declining reading habits of students in Philippine literature classes - Jason V. Chavez; Pearly Jade E. Samilo; Neña Vanessa A. Cabiles; Joseph B. Quinto; Erwin F. Maturan; Salita D. Dimzon; Leizl Joy A. Alzate; Ma. Theresa L. Eustaquio; Josephine L. Cruz; Haydee G. Adalia (Environment and Social Psychology, 2025)
The decline in students’ reading engagement poses a significant challenge to literature instruction, particularly in Philippine Literature courses that aim to foster cultural awareness, empathy, and critical thinking. This qualitative study explored college instructors’ perspectives on the declining reading habits of students in Philippine Literature classes. Sixteen instructors from public and private higher education institutions across Luzon, Visayas, and Mindanao participated in semi-structured interviews. Findings revealed three major factors contributing to students’ disengagement: reliance on summarized content and digital shortcuts, diminished motivation and perceived relevance of literature, and the influence of digital distractions and cognitive fatigue. Instructors attributed these issues to both environmental and psychological factors, aligning with Bandura’s Social Cognitive Theory, which emphasizes the reciprocal influence of personal beliefs, behavior, and environment. Despite these challenges, instructors demonstrated adaptive responses through contextualized teaching, integration of multimedia and creative outputs, and scaffolding techniques that make reading more accessible and meaningful. The study concludes that addressing the decline in reading habits requires a systemic and multi-level approach that includes institutional support, cross-disciplinary collaboration, and renewed pedagogical innovation. By reimagining literature instruction as an interactive and reflective process, educators can revitalize students’ engagement with Philippine literary texts and reaffirm the role of reading as a transformative cultural and intellectual practice.